Penentuan Prioritas Penanganan Berdasarkan Kinerja Fisik Bangunan Irigasi DI Tumpukrenteng, Kabupaten Malang - Cucuk Rusdiyanto; Yurnalisdel Yurnalisdel; M. Sa'dillah (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
The reliability of irrigation infrastructure plays a crucial role in supporting agricultural productivity and the sustainability of water distribution. Over time, the physical components of irrigation networks are prone to degradation due to aging, hydraulic loads, sedimentation, and limited maintenance. This study aims to assess the existing physical condition and analyze the physical performance of irrigation structures in the Tumpukrenteng Irrigation District, Turen Subdistrict, Malang Regency, which serves approximately 98 hectares of agricultural land. The study focuses on physical infrastructure aspects, including main structures, conveyance channels, and ancillary structures. The research methodology involved field inspections, visual surveys of structure conditions, and direct measurements of damage levels supported by secondary technical data. The inventory data were analyzed using a weighting method based on the Irrigation System Performance Index standards, with an emphasis on physical infrastructure indicators. The results of the study indicate that, in general, the irrigation network remains in good condition; however, there are some localized damages such as minor cracks, surface peeling, sedimentation, and the growth of wild vegetation on certain canals and structures. These conditions have the potential to reduce flow efficiency and increase water loss if not addressed promptly. The physical performance metrics obtained indicate that the irrigation system is still functional but requires periodic maintenance and targeted repairs. In conclusion, this study provides a quantitative and objective assessment of the physical performance of the irrigation network, which serves as a basis for determining priorities for ongoing maintenance and rehabilitation.